PENERAPAN PENERAPAN MEDIA PEMBELAJARAN CROSSWORLD PUZZLE DALAM MENINGKATKAN ASPEK PERKEMBANGAN KOGNITIF PESERTA DIDIK MADRASAH IBTIDAIYAH - Hestyaningsih, Lika (STIT Pemalang, 2025)
This research aims to explain the application of using Cross world learning media in enhancing the cognitive development aspects of madrasah ibtidiyah students. This study uses qualitative research methods with a qualitative descriptive approach. The results of this study indicate that the use of crossword puzzles as a learning medium is effective in enhancing various cognitive aspects of elementary school students. The activity of solving crossword puzzles not only helps students improve their memory and understanding of concepts but also stimulates critical and creative thinking skills. In an interactive and enjoyable way, students become more engaged in the learning process, which contributes to an increase in their learning motivation.